2023
DOI: 10.1038/s41598-023-47015-w
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus in pediatric patients with severe acute respiratory infections in Senegal: findings from the 2022 sentinel surveillance season

Mamadou Malado Jallow,
Moussa Moise Diagne,
Samba Niang Sagne
et al.

Abstract: In 2022, many regions around the world experienced a severe respiratory syncytial virus (RSV) epidemic with an earlier-than-usual start and increased numbers of paediatric patients in emergency departments. Here we carried out this study to describe the epidemiology and genetic characteristics of RSV infection in patients hospitalized with severe acute respiratory infections in 2022. Samples were tested for RSV by multiplex real time reverse transcription polymerase chain reaction. Subsequently, a subset of RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
3
4
0
Order By: Relevance
“…Full-length sequencing of other structural proteins showed a high degree of similarity with the reference strain. In agreement with a previous study, a small number of amino acid changes were identified in the internal proteins ( Jallow et al, 2023 ). The L56I, K570R, I715V, R1759K, and A1787E substitutions were located in the conserved enzymatic regions RdRp, Cap, and MT of L protein, which are potential targets for inhibitor development ( Gilman et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Full-length sequencing of other structural proteins showed a high degree of similarity with the reference strain. In agreement with a previous study, a small number of amino acid changes were identified in the internal proteins ( Jallow et al, 2023 ). The L56I, K570R, I715V, R1759K, and A1787E substitutions were located in the conserved enzymatic regions RdRp, Cap, and MT of L protein, which are potential targets for inhibitor development ( Gilman et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…During the study period, RSV affected all age groups across the population, with much more frequent involvement in children aged < 5 years, especially those under 2 years. In line with many reports, the rate of RSV infection was highest in the youngest age group (up to 1 year) and decreased with increasing age due to the development of immunity after repeated infections ( Jepsen et al, 2018 ; Jallow et al, 2023 ). Administration of the recently approved Abrysvo vaccine during pregnancy could protect infants against LRTI from birth to 6 months of age (EMA; Saso and Kampmann, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This outcome is similar to that reported by other authors [31,56,57]. However, similar to the global trend that was recorded from 2017 to 2018 by Tabor et al [58] and other studies [59][60][61], the HRSV B group was very slightly predominant over the HRSV A group in our study. All HRSV B viruses in this study were clustered with the GB5 genotype, which mostly has a specific 60-nucleotide duplication in the HVR2 domain.…”
Section: Discussionsupporting
confidence: 93%
“…These GA2 genotypes were all classified into the GA2.3 subgenotype and the GA2.3.5 genetic lineage. These genotypes have been identified in the USA, France, Italy, and Senegal in studies published by Goya et al, Coppée et al,Tramuto et al,and Jallow et al,respectively [59,60,[63][64][65]. Furthermore, it is important to note that the GB5.0.5a genetic lineage highlighted in this study was already circulating in the Cameroonian population during the pre-pandemic years [34]; hence, there were no identifiable changes in HRSV B since the onset of the COVID-19 pandemic, which could explain the change in viral spread.…”
Section: Discussionmentioning
confidence: 99%